Lac Cultivation as a Pathway to Prosperity: A Success Story from Ranchi, Jharkhand - , Auindrila Biswas; , Bhavna Sinha; , Sourakanti Sarkar; , Debasmita Baruah; , Arnab Roy (Archives of Current Research International, 2024)
Lac is a commercially significant cash crop that serves as a vital source of income for millions of economically disadvantaged farmers residing in tribal-dominated forest and sub-forest regions of the country. Due to the worldwide trend towards the usage of natural products, there is a consistent demand for bio-degradable and non-toxic products made from lac in the market. However, production of this economically vital commodity is declining over the years because of alterations in precipitation patterns, recurrent droughts and floods, heightened intensity and frequency of cold waves, and surges in insect pests and diseases. Jharkhand, the largest lac producer state in the country has reflected a disappointing growth rate at -0.33% over the period of 2011-12 to 2021-22. The benefit cost ratio of 2.43 by selling stick lac to middlemen, clearly reflects the high profitability nature of lac cultivation. Considering the economic benefits of the producers and the global demand for safe natural lac cultivation, enhancement in various aspect is required.